Look, no hands: A perceptual task shows that number magnitude induces shifts of attention - Nicholls, M.; Loftus, Andrea; Gevers, W. (Springer New York LLC, 2008)
The mental representation of numbers along a line oriented left to right affects spatial cognition, facilitating responses in the ipsilateral hemispace (the spatial–numerical association of response codes [SNARC] effect). We investigated whether the number/space association is the result of an attentional shift or response selection. Previous research has often introduced covert left/right response cues by presenting targets to the left or the right. The present study avoided left/right cues by requiring forced choice upper/lower luminance discriminations to two mirror-reversed luminance gradients (the grayscale task). The grayscale stimuli were overlaid with strings of (1) low numbers, (2) high numbers, and (3) nonnumerical characters. In Experiment 1, 20 dextrals judged the number’s magnitude and then indicated whether the upper/lower grayscale was darker. Results showed leftward and rightward attentional biases for low and high numbers, respectively. Demands to process numbers alonga left/right line were made less explicit in Experiment 2 (N 5 18 dextrals), using (1) a parity judgment and (2) arbitrary linguistic labels for top/bottom. Once again, a spatial congruency effect was observed. Because the response (up/down) was orthogonal to the dimension of interest (left/right), the effect of number cannot be attributed to late-stage response congruencies. This study required unspeeded responses to stimuli presented in free vision, whereas other experiments have used speeded responses. Understanding the time course of number–space effects may, therefore, be important to the debate associated with response selection.